Penggunaan Media Lagu Untuk Meningkatkan Pemahaman Terhadap Kekerasan Seksual Anak Usia 4-6 Tahun(Systematic Literature Review) - Vika Lailah Lestari; Aris Rahmadani, Ni Kadek (Program Studi pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2026)
Sexual violence against children is a criminal act that must be addressed and is a deviant activity carried out forcibly by adults on children. This article presents a systematic literature review aimed at examining the effectiveness of using songs to enhance the understanding of sexual violence among children aged 4-6 years. The method used in this study is a Systematic Literature Review (SLR). The literature was obtained from electronic databases such as Google Scholar; journal articles that match the Population, Issue, Outcome (PIO), children aged 4-6 years, full-text journal manuscripts; and intervention study research articles (RCT, quasi-experimental, pre-post, pilot, RND), qualitative study, quantitative study using songs as a key component for sexual violence prevention, published 2015 – 2025. The Preferred Reporting Items for Systematic Review and Meta-analytic (PRISMA) method was used for article selection, and descriptive analytic techniques were used for analysis. A total of 619 articles were considered relevant to the topic, and 10 articles were included based on the inclusion criteria. The study results indicate that the effective use of songs can improve early childhood sexual education understanding. Children can recognize family members, understand the names of body parts, learn how to care for and protect themselves, recognize differences in gender characteristics, and know which body parts others may and may not see and touch. Schools have a very important in providing sexual education to young children. Sexual education in early childhood is an important step in preventing sexual violence and should be implemented using methods appropriate to the child’s development at ages 4–6, namely through songs.